The canoe and the saddle, adventures among the northwestern rivers and forests, and Isthmiana. - Winthrop, Theodore, 1828-1861 (Ticknor & Fields, 1863)
A narrative of travel in Washington Territory in 1853 and on the Isthmus of Panama in the preceding year.